Clays and Clay Minerals, Vol. 56, No. 5, 579–595, 2008. - Furquim, Sheila Aparecida Correia; Graham, Robert C.; Barbiero, Laurent; Neto, Jose Pereira De Queiroz; Valles, Vincent (The Clay Mineral Society, 2008)
Smectite formation in alkaline-saline environments has been attributed to direct precipitation from solution and/or transformation from precursor minerals, but these mechanisms are not universally agreed upon in the literature. The objective of this work was to investigate the mineralogy of smectites in the soils surrounding a representative alkaline-saline lake of Nhecolaˆndia, a sub-region of the Pantanal wetland, Brazil, and then to identify the mechanisms of their formation. Soils were sampled along a toposequence and analyzed by X-ray diffraction, transmission electron microscopy-energy dispersive X-ray analysis, and inductively coupled plasma-mass spectrometry. Water was collected along a transect involving the studied toposequence and equilibrium diagrams were calculated using the databases PHREEQC and AQUA. The fine-clay fraction is dominated by smectite, mica, and kaolinite. Smectites are concentrated at two places in the toposequence: an upper zone, which includes the soil horizons rarely reached by the lake-level variation; and a lower zone, which includes the surface horizon within the area of seasonal lake-level variation. Within the upper zone, the smectite is dioctahedral, rich in Al and Fe, and is classified as ferribeidellite. This phase is interstratified with mica and vermiculite and has an Fe content similar to that of the mica identified. These characteristics suggest that the ferribeidellite originates from transformation of micas and that vermiculite is an intermediate phase in this transformation. Within the lower zone, smectites are dominantly trioctahedral, Mg-rich, and are saponitic and stevensitic minerals. In addition, samples enriched in these minerals have much smaller rare-earth element (REE) contents than other soil samples. The water chemistry shows a geochemical control of Mg and saturation with respect to Mgsmectites in the more saline waters. The REE contents, water chemistry, and the presence of Mg-smectite where maximum evaporation is expected, suggest that saponitic and stevensitic minerals originate by chemical precipitation from the water column of the alkaline-saline lake.
Mineralogy And Genesis Of Smectites In An Alkaline-saline Environment Of Pantanal Wetland, Brazil
gsccm56511-fur.pdf - 516KB
Keywords: Periodicals; Geology; Chemical Precipitation; Ferribeidellite; Mg-smectite; Mica-smectite Interstratification; Neoformation; Transformation; Trioctahedral Smectite; Saline Lake